2013
DOI: 10.2139/ssrn.2320464
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility, Multi-Faceted Job-Products, and Employee Outcomes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 57 publications
6
70
0
Order By: Relevance
“…Whereas we faced constraints from our research sponsors on how many variables we could include, and our sample size prohibited us from testing too complex of a model, we did attempt to choose as control variables those we felt were among the best "contenders" for potentially confounding our results.4 In our sample, non-profits included educational institutions, government agencies, health care organizations, and social service agencies.5 Considerable CSR research includes data from non-profit organizations (e.g.,Du, Bhattacharya, & Sen, 2015;De Roeck, Marique, Stinglhamber, & Swaen, 2014;Gatignon-Turnau & Mignonac, 2015).6 Note that in response to a reviewer comment, we re-ran all analyses using data from employees working for for-profit organizations only, and all results were consistent with those reported below.…”
supporting
confidence: 52%
“…Whereas we faced constraints from our research sponsors on how many variables we could include, and our sample size prohibited us from testing too complex of a model, we did attempt to choose as control variables those we felt were among the best "contenders" for potentially confounding our results.4 In our sample, non-profits included educational institutions, government agencies, health care organizations, and social service agencies.5 Considerable CSR research includes data from non-profit organizations (e.g.,Du, Bhattacharya, & Sen, 2015;De Roeck, Marique, Stinglhamber, & Swaen, 2014;Gatignon-Turnau & Mignonac, 2015).6 Note that in response to a reviewer comment, we re-ran all analyses using data from employees working for for-profit organizations only, and all results were consistent with those reported below.…”
supporting
confidence: 52%
“…Since, CSR can represent a good image of the organization, it is likely for employees to identify strongly and feel proud working in the organization having such positive social values (Brammer, Millington, & Rayton, 2007). Prior research also supported the linkage between CSR perception and positive work attitudes (Du, Bhattacharya, & Sen, 2015;Turker, 2009;You et al, 2013). Given all the theoretical and prior supports, the following hypotheses are proposed:…”
Section: Role Of Csr Perception To Work Attitudementioning
confidence: 90%
“…In the context of small and medium‐sized enterprises of fashion industries, studies have found that CSR activities significantly improve the innovation processes of firms, both from the technical and organizational points of view (Battaglia et al, ). Scholars have therefore indicated that many organizations across the globe are increasingly leveraging CSR to gain CA and achieve long‐term success (Du, Bhattacharya, & Sen, ; Flammer, ; Porter & Kramer, ).…”
Section: Literature Reviewmentioning
confidence: 99%